Pulmonary Glandular Papilloma with Abundant Extracellular Mucin and BRAF V600E, AKT1 E17K Mutations: A Case Report - Yang, Zhenyun; Song, Fengyu; Zhong, Jin (Archives of Clinical and Medical Case Reports, 2022)
Pulmonary glandular papillomas of the lung are very rare benign pulmonary tumors with only a few cases described in the literature. It is challenging to make the diagnosis based on clinical features, imaging findings and small core biopsies. Here we present a case of pulmonary glandular papilloma with abundant extracellular mucin, which was initially diagnosed as mucinous invasive adenocarcinoma with small core biopsy. Differential diagnosis and its molecular analysis are discussed. Physician should think about the possibility of glandular papilloma for any pulmonary nodules.